LOCAL EMPOWERMENT APPROACH IN PROCESSING COCONUT SHELL WASTE IN SEBAMBAN VILLAGE, EAST KOTAWARINGIN REGENCY - Naya, Ketut; Ludang, Yetrie; Indrajaya, Kusnida; Edy Setiawan, Wahyu; Herianto; Sinaga, Soaloon (Acta Scientiae et Intellectus, 2024)
This paper is a preliminary research report on community empowerment in coconut shell waste management. As a potential empowerment, the research method used is qualitative, which can then be utilized, especially for workers in Sebamban Village, East Kotawaringin Regency. Through empowerment with a local approach, a potential job development in the handicraft sector is obtained. In the course of the development of handicrafts in the area, handicrafts can be understood from several points of view, namely based on the type of handicraft product, form, actor, and scale of production, and materials and working techniques of the handicraft product. The results of this study are expected to be of benefit to the implementation of skills training by the local manpower office and other training implementers. In addition, the results of this study are also expected to be of benefit to policy makers for the implementation of training and for related parties in an effort to achieve maximum training results.